Particle manipulation by adhere method as travelling surface acoustic wave - Nor Halim, Nur Amiera (2021)
Surface acoustic wave (SAW) is waves that propagate on the surface of the substrate. The propagating wave generated by applying the alternating voltage across electrodes on piezoelectric substates. By the propagating waves, it can be used for the separation of particles. There are two important parameters of SAW to be used in particle manipulation which are the piezoelectric substrate (PZT) and interdigitated electrode (IDE). For this project, the channel for particle manipulation will be part of the device. For SAW have two types which is Travelling surface acoustic wave (TSAW) and Standing surface acoustic wave (SSAW). TSAW device involves one IDE. In this project, the working principle of the TSAW device has been demonstrated in microfluidic systems with the alternative method. The previous method of fabrication has some disadvantages which is affect the fabrication time besides cannot vary finger dimension because of the electrode have been built in the piezoelectric substrate. In this project, adhere method has been used to replace the conventional method that involves IDE and piezoelectric substrates by using PZT substrate. In this work SAW generated on the piezoelectric substrate using interdigitated electrode fabricated using ITO coated glass in contact with each other to stimulate the wave propagation. The generation of TSAW have been observed concerning the size of interdigitated ITO glass electrode IDE needed to find the optimum time for the SAW force reached as for the best point of velocity and the best output voltage with low loss, which can generate stable TSAW. In this project, shows that 20s is the maximum point for SAW applying force to manipulate the particles. Besides that, the best distance for the best output voltage with low loss is 3 cm which is suitable for this adhere method.